Long-term outcomes of implant-based dental rehabilitation in head and neck cancer patients after reconstruction with the free vascularized fibula flap. Issue 9 (September 2021) - Lodders, Johannes N.; Leusink, Frank K.J.; Ridwan-Pramana, Angela; Winters, Henri A.H.; Karagozoglu, K. Hakki; Dekker, Hannah; Forouzanfar, Tymour; Schulten, Engelbert A.J.M.
Abstract: The study aimed at evaluating, comprehensively, implant-based dental rehabilitation in head and neck cancer patients after maxillofacial reconstruction with a vascularized free fibula flap (FFF). Data were obtained by retrospectively reviewing the medical records of patients treated in Amsterdam UMC-VU Medical Center. Dental implant survival and implant success according to the Albrektsson criteria were analyzed. Additionally, prosthetic-related outcomes were studied, with a focus on functional dental rehabilitation. In total, 161 implants were placed in FFFs, with a mean follow-up of 4.9 years (range 0.2–23.4). Implant survival was 55.3% in irradiated FFFs and 96% in non-irradiated FFFs. Significant predictors for implant failure were tobacco use and irradiation of the FFF. Implant success was 40.4% in irradiated FFFs and 61.4% in non-irradiated FFFs, mainly due to implant failure and non-functional implants. Implant-based dental rehabilitation was started 45 times in 42 patients, out of 161 FFF reconstructions (27.9%). Thirty-seven patients completed the dental rehabilitation, 29 of whom achieved functional rehabilitation. Irradiation of the FFF negatively influenced attainment of functional rehabilitation. For patients with functional rehabilitation, the body mass index varied at different timepoints: FFF reconstruction, 24.6; dental implantation 23.5; and after placing dental prosthesis, 23.9. Functional implant-based dental rehabilitation, if started, can be achieved in the majority of head and neck cancer patients after FFF reconstruction. Actively smoking patients with an irradiated FFF should be clearly informed about the increased risk for implant and prosthetic treatment failure.